Composition of lymphocyte subpopulations in normal and mildly reactive peripheral lymph nodes in cats. Issue 2 (February 2022) - Rütgen, Barbara C; Baszler, Elisabeth; Weingand, Nicole; Wolfesberger, Birgitt; Baumgartner, Daniel; Hammer, Sabine E; Groiss, Sandra; Fuchs-Baumgartinger, Andrea; Saalmüller, Armin; Schwendenwein, Ilse
Objectives: Flow cytometric (FCM) immunophenotyping of lymphoid tissue aspirates is an available adjunct for feline lymphoma diagnostics. Reference data have only been established for feline peripheral blood. Studies investigating the composition of normal and mildly reactive feline lymph nodes (LNs) are lacking. The aim of this prospective study was to establish reference data for lymphocyte subpopulations in normal and mildly reactive feline peripheral LNs using a standardised multicolour panel of antibodies. Methods: Macroscopically inconspicuous mandibular and/or popliteal LNs from 31 adult cats, which were euthanased for reasons other than haematological diseases, were excised and processed within 5 h after death. Multicolour flow cytometry using eight different feline-specific, anti-canine and human cross-reactive monoclonal antibodies used in current diagnostic marker panels was performed after cytological exclusion of pathological states and complemented by lymphocyte clonality testing, histopathology and immunohistochemistry (IHC) to ensure the absence of lymphoid disease. Results: Of 31 cats, the immunophenotyping data of 24 individuals could be included as histopathology and clonality testing excluded a pathological condition. Lymphocyte populations showed the following positive antibody reactions: CD18 + 86.3% ± 13.86%, CD3 + 54.81% ± 11.10%, CD5 + 57.39% ± 12.66%, CD21 + 40.42% ± 12.40%, CD79alphacy + (CD79αcy) 30.41% ± 13.49% and CD14 + 0.75% ± 1.35%. There were 30.88% ± 13.48% CD4 + and 12.91% ± 6.68% CD8 + cells. Cytology revealed a mixed population of mostly lymphoid cells in all samples. The absence of a monoclonal/oligoclonal neoplastic population was confirmed by lymphocyte clonality testing. Histopathology and IHC showed a normal or mildly reactive pattern in all cases. Conclusions and relevance: This study establishes FCM immunophenotyping data of lymphocyte populations of normal and mildly reactive feline peripheral LNs. For the first time, anti-CD5, CD4, CD8 and CD21 reference data in normal and mildly reactive feline peripheral LNs are presented. CD18, CD3, CD14 and CD79αcy have been used to establish reference data for the first time in any feline material.